2012
DOI: 10.1515/1932-0191.1068
|View full text |Cite
|
Sign up to set email alerts
|

Mental Practice is Modifiable: Changes in Perspective Maintenance and Vividness Post-Stroke

Abstract: This exploratory study investigated effects of a mental practice (MP) intervention on imagery vividness and perspective maintenance in post-stroke subjects. Additionally, the relationship between internal and external imagery vividness and kinesthetic imagery was examined. Data were drawn from 17 persons participating in a RCT investigating the effects of perspective use during MP on post-stroke recovery. The Vividness of Movement Imagery Questionnaire-2 (VMIQ-2) and a self-report perspective rating scale were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…For example, a study by Callow, Roberts, and Fawkes () has demonstrated that downhill skiers who imagined themselves completing a downhill ski‐slalom course experienced increases in vividness of imagery. Extending these findings, research by Nobbe, Nilsen, and Gillen () has highlighted that participants who used mental imagery twice per week for six consecutive weeks demonstrated a 22 per cent increase in imagery vividness.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…For example, a study by Callow, Roberts, and Fawkes () has demonstrated that downhill skiers who imagined themselves completing a downhill ski‐slalom course experienced increases in vividness of imagery. Extending these findings, research by Nobbe, Nilsen, and Gillen () has highlighted that participants who used mental imagery twice per week for six consecutive weeks demonstrated a 22 per cent increase in imagery vividness.…”
Section: Introductionmentioning
confidence: 85%
“…As an exploratory goal, using latent growth curve analyses, we also investigated whether participants in the mental imagery condition would significantly differ from themselves and the meditation condition over time . That is, we explored whether the mental image of future self would become significantly more vivid over time (Callow et al, ; Nobbe et al, ) for participants in the mental imagery condition. As a consequence, we explored whether these participants would feel more empathy for that self (Johnson et al, ) than those in the present‐focused meditation condition.…”
Section: Introductionmentioning
confidence: 99%
“…Some have proposed that mentally rehearsing a task from within the body may include a sense of movement (Epstein, 1980;Hale, 1982;Harris & Robinson, 1986). While external imagery, on the other hand, has been proposed as primarily a visual approach (Hinshaw, 1992), later studies have shown that imagers are able to form kinesthetic images equally well with either internal or external perspectives (Cumming & Ste-Marie, 2001;Gates, DePalma, & Shelley, 2003;Glisky et al, 1996;Hardy & Callow, 1999;Nobbe, Nilsen, & Gillen, 2012;White & Hardy, 1995). Interestingly, Callow and Hardy (2004) even demonstrated that, depending on whose execution is imagined from the external perspective (i.e., oneself or another person), kinesthetic imagery has a stronger relationship with external than with internal imagery.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study by Callow, Roberts, and Fawkes (2006) has demonstrated that downhill skiers who imagined themselves completing a downhill ski-slalom course experienced increases in vividness of imagery. Extending these findings, research by Nobbe, Nilsen, and Gillen (2012) has highlighted that participants who used mental imagery twice per week for six consecutive weeks demonstrated a 22% increase in imagery vividness. While the scope of these results is limited by small sample sizes, both of these studies empirically support the idea that adopting a consistent mental imagery practice can be beneficial in increasing imagery vividness.…”
Section: From Imagination To Imagery: Fostering the Temporally Extendmentioning
confidence: 86%
“…Although these results are promising for procrastination interventions, this method of using individual sessions with avatars of future self can be costly and may not be available to social institutions that would benefit the most from this technology, such as schools, health sectors, and workplaces. However, the research reported by Hershfield and his colleagues offers a strong theoretical foundation for exploring how mental imagery, a cognitive tool with which every human is equipped, can increase future self's vividness (Callow, Roberts, & Fawkes, 2006;Nobbe, Nilsen, & Gillen, 2012), emotional states (Kosslyn et al, 2001;Damasio, 1999;Holmes et al, 2006), foster empathy (Johnson, Cushman, et al, 2013), and in turn, increase self-continuity .…”
Section: From Imagination To Imagery: Fostering the Temporally Extendmentioning
confidence: 99%